The restorer gene for soybean M‐type cytoplasmic male sterility, Rf‐m, is located in a PPR gene‐rich region on chromosome 16. Issue 3 (18th March 2016) - Wang, Dagang; Zhang, Lei; Li, Jiekun; Hu, Guoyu; Wu, Qian; Jiang, Haiyan; Huang, Zhiping
Abstract: Over the past decade, M‐type cytoplasmic male sterility (CMS) line W931A and a variety of restorer lines have been exploited for the release of hybrid seeds in soybean ( Glycine max ). However, the identities of restorer genes in the nuclei of soybean restorer lines are still unclear. In this study, we analysed the inheritance pattern of restorer locus Rf‐m from restorer line WR016 and constructed a high‐resolution map of this locus. Results showed that Rf‐m in WR016 is a monogenic dominant gene located within a 162.4‐kb region on chromosome 16, which is flanked on each side by new developed simple sequence repeat (SSR) markers GmSSR1602 and GmSSR1610 at a distance of 0.11 and 0.25 cM, respectively. Nineteen open reading frames (ORFs) were predicted in this region. Of these, seven genes arranged in tandem on chromosome 16 encode pentatricopeptide repeat (PPR) proteins, which is similar to other reported restorer loci in plants. These results lay a solid foundation for map‐based cloning of the Rf‐m gene and will be helpful for marker‐assisted selection of elite CMS restorer lines.